2014
DOI: 10.1117/1.jbo.19.2.026012
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic breast phantoms with physiological water, lipid, and hemoglobin content for near-infrared spectral tomography

Abstract: Abstract. Breast mimicking tissue optical phantoms with sufficient structural integrity to be deployed as standalone imaging targets are developed and successfully constructed with biologically relevant concentrations of water, lipid, and blood. The results show excellent material homogeneity and reproducibility with inter-and intraphantom variability of 3.5 and 3.8%, respectively, for water and lipid concentrations ranging from 15 to 85%. The phantoms were long-lasting and exhibited water and lipid fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…This 3-D ring-scanning equipment remains being calibrated, and it is anticipated that anthropomorphic breast phantoms with physiological content 28 and clinical trials will be reported in the future. First, the image reconstruction for various synthesized scanning situations justified the proposed 3-D NIR ring-scanning equipment through (1) comparing with fixed-channel equipments and (2) sliced image reconstruction for the 3-D task.…”
Section: Resultsmentioning
confidence: 99%
“…This 3-D ring-scanning equipment remains being calibrated, and it is anticipated that anthropomorphic breast phantoms with physiological content 28 and clinical trials will be reported in the future. First, the image reconstruction for various synthesized scanning situations justified the proposed 3-D NIR ring-scanning equipment through (1) comparing with fixed-channel equipments and (2) sliced image reconstruction for the 3-D task.…”
Section: Resultsmentioning
confidence: 99%
“…This is a very important scenario to determine the presence of tumors. The phantoms developed in [49] were long-lasting and demonstrated water and lipid fractions that were consistent to within 5% of their original content measured 2 weeks after their formation. A breast-shaped three-layered model of adipose, fibroglandular, and malignant tissues was created with water content ranging from 30% for the adipose simulant to 80% for the tumor.…”
Section: Rmsmentioning
confidence: 99%
“…An antenna array was used, in which one of the antenna was transmitting through a 3D breast model and other were receiving the backscattered pulse. The dielectric properties used in [49] for breast phantoms are given in Table 15. The cross-section of FDTD 3D hemisphere breast model is shown in Figs.…”
Section: Numerical Breast Phantoms (Computer Models)mentioning
confidence: 99%
See 2 more Smart Citations